Successful Immunotherapy for Pancreatic Cancer in a Patient With TSC2 and SMAD4 Mutations: A Case Report - Ye, Yanghui; Zheng, Song (Frontiers in Immunology, 2021)
Background: Pancreatic cancer has a poor prognosis, and it is traditionally treated with chemotherapy. Fortunately, immunotherapy has rapidly changed the landscape of solid tumor treatment, and improving the survival of cancer patients. However, pancreatic cancer is non-immunogenic, and single agent immunotherapies are unfavorable to its prognosis. Case presentation:Here, we report a case of stage IV pancreatic cancer in a patient with TSC2 and SMAD4 mutations treated with immunotherapy when the disease progressed after multi-line chemotherapy. Next generation sequencing (NGS) confirmed the presence of TSC2 and SMAD4 mutations and microsatellite stability (MSS). When the disease progressed after chemotherapy, a combination strategy was devised consisting of chemotherapy (S-1) and sintilimab. The patient had a partial response to therapy with this regimen, the lesions were significantly reduced and nearly disappeared. In metastatic pancreatic cancer, responses of this magnitude are rarely seen. Conclusions: This outcome reveals that this combination can be effective in treating metastatic pancreatic cancer, especially in pancreatic cancer patients with SMAD4 and TSC2 mutations. This may help increase the use of this therapy in large-scale clinical research.